APPLICATION OF THE MFEP METHOD IN DETERMINING STUDENTS' INCLUDING LEARNING DIFFICULTIES TEACHING - Ari Sahbana Purba Ari Sahbana Purba; Hambali; Febby Maddona Yumma (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
Inclusive students are children with special needs who participate in general or ordinary classes with other children, such as children who have difficulty seeing or hearing, cannot walk, have autism, or are slower to learn. when organizing the teaching and learning process Sometimes in the process of selecting students there are often mistakes and not right on target so that there are problems when determining students who are classified as inclusive students during examinations at school. In this study, the Multi Factor Evaluation Process (MFEP) method was chosen to determine the decision assessment to determine the inclusion of students with teaching and learning difficulties. This method is more efficient than other methods included in the completion of the Multi Attribute Decision Making (MADM). Utilization of the Multi Factor Evaluation Process (MFEP) requires a relatively shorter calculation time. The calculation system for the MFEP method with calculations carried out by SMK AL AZMI Tanjung Asri was carried out using the Microsoft Excel application, so the final results were close to the same, namely the method with calculations that began with giving weights to each criterion that had been determined by SMK AL AZMI Tanjung Asri processed by using the MFEP method to get the ranking results. the MFEP method of assessment that has been carried out through many calculation processes, ranging from weighting the values ​​of all criteria and determining grades to getting candidates for Determining Inclusive Students with Teaching and Learning Difficulties at SMK AL AZMI Tanjung Asri. Keywords: Student, inclusion, Multi Factor Evaluation Process (MFEP), score.